Social Media and Public Participation in Nigeria: Challenges and Possibilities - Muse, Sulaimon Adigun; Muse, Sulaimon Adigun (Advances in Social Sciences Research Journal, 2014)
The advent of social media in the world of information has added a very unique dimension to the participation of more people in those affairs that particularly has direct effects to their day-to-day lives and survival. Social media has already occupied those spaces that were hitherto un-occupied by the owned media. This is against the back drop of the aftermath effects of social media on regime change in the world, particularly the Arab springs and other hot spots in the world. This has equally brought human race together in a more globalised world. The aim of this paper is to look at social media and public participation in Nigeria, vis-à-vis the challenges and possibilities. The paper shall be pivoted on the theory of participatory democracy. It is mainly a qualitative paper; hence no primary data will be made used of.